2015
DOI: 10.1130/l437.1
|View full text |Cite
|
Sign up to set email alerts
|

Lateral extrusion, underplating, and out-of-sequence thrusting within the Himalayan metamorphic core, Kanchenjunga, Nepal

Abstract: Integrated pseudosection modeling and monazite petrochronology of paragneiss from the Kanchenjunga region of northeastern Nepal reveal the presence of cryptic tectonometamorphic discontinuities within the Himalayan metamorphic core. These new data outline a series of thrust-sense structures that juxtapose rocks that generally record a protracted history of early Eocene to latest Oligocene-early Miocene (ca. 41-23 Ma) prograde metamorphism and lateral extrusion against others that typically record short prograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 105 publications
4
68
0
Order By: Relevance
“…Here, monazite ages record cooling of the MCT sheet from 20 to 16 Ma (Corrie & Kohn, ). While these examples and others support models in which the GHS was assembled through in‐sequence thrust stacking (Ambrose et al., ; Carosi et al., , ; Corrie & Kohn, ; Kohn, ; Kohn et al., ; Larson et al., ; Montomoli et al., , ), they also indicate that the number, structural position, age and duration of intra‐GHS thrusts is highly variable. Corrie and Kohn () argued that the presence of lateral ramps along‐strike or non‐continual thrust planes could explain synchronous movement of thrusts at different structural levels.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Here, monazite ages record cooling of the MCT sheet from 20 to 16 Ma (Corrie & Kohn, ). While these examples and others support models in which the GHS was assembled through in‐sequence thrust stacking (Ambrose et al., ; Carosi et al., , ; Corrie & Kohn, ; Kohn, ; Kohn et al., ; Larson et al., ; Montomoli et al., , ), they also indicate that the number, structural position, age and duration of intra‐GHS thrusts is highly variable. Corrie and Kohn () argued that the presence of lateral ramps along‐strike or non‐continual thrust planes could explain synchronous movement of thrusts at different structural levels.…”
Section: Introductionmentioning
confidence: 72%
“…One or more thrust‐sense intra‐GHS tectonometamorphic discontinuities have been located in 17 different transects in the Himalaya, spanning from just west of the Nepali‐Indian border through Bhutan (Ambrose et al., ; Carosi, Montomoli, Rubatto, & Visonà, ; Carosi et al., ; Corrie & Kohn, ; Cottle et al., ; Larson et al., ; Kohn, ; Kohn, Wieland, Parkinson, & Upreti, ; Montomoli, Iaccarino, Carosi, Langone, & Visonà, ; Montomoli et al., ). Evidence from petrographic and kinematic observations led some early researchers to argue that intra‐GHS discontinuities are late‐stage, post‐peak‐metamorphic features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, recent studies across the central and eastern Himalaya have revealed evidence that upper structural levels of the GH achieved granulite, and possibly earlier eclogite facies conditions prior to exhumation (e.g. Groppo et al ., ; Grujic et al ., ; Guilmette et al ., ; Warren et al ., ; Ambrose et al ., ; Zhang et al ., ). The upper‐GH samples from central and eastern Bhutan in this study do not contain orthopyroxene or abundant K‐feldspar and muscovite, observed in nearly all samples (the exception being BU12‐212B), are interpreted to be part of the peak assemblage (Figs ).…”
Section: Discussionmentioning
confidence: 97%
“…These strike‐parallel discontinuities, identified at various structural levels within the HMC (e.g. Ambrose et al., ; Carosi, Montomoli, Rubatto, & Visonà, ; Carosi et al., ; Corrie & Kohn, ; Imayama et al., ; Iaccarino et al., ; Larson & Cottle, ; Larson et al., ; Martin, Ganguly, & DeCelles, ; Montomoli et al., ; Rubatto, Chakraborty, & Dasgupta, ; Wang, Rubatto, & Zhang, ; Wang, Zhang, et al., ; Wang et al., ; Warren et al., ; Yakymchuk & Godin, and others), rarely have an associated field expression (Larson & Cottle, ; Warren et al., ) and are typically recognized on the basis of abrupt breaks in P–T–t paths of adjacent rock packages (Ambrose et al., ; Larson et al., ; Rubatto et al., ). Whilst most of these discontinuities have been investigated based on a single type of analysis or the combination of few analytical methods (see Larson et al., and references therein), which range from field‐based structural identification to laboratory‐based techniques such as thermobarometry (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ambrose et al., ; Corrie & Kohn, ; Khanal, Robinson, Kohn, & Mandal, ; Larson, Cottle, & Godin, ; Warren et al., ), P–T–t phase equilibria modelling (e.g. Ambrose et al., ; Iaccarino et al., ; Larson et al., ; Rapa et al., ; Wang et al., ; Warren et al., ), or quartz crystallographic fabric analysis (e.g. Larson & Cottle, ; Yakymchuk & Godin, ), rarely have they been studied in an integrated approach (e.g.…”
Section: Introductionmentioning
confidence: 99%